2019
DOI: 10.1126/sciadv.aav8141
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite nanowire–block copolymer composites with digitally programmable polarization anisotropy

Abstract: One-dimensional (1D) nanomaterials with highly anisotropic optoelectronic properties are key components in energy harvesting, flexible electronics, and biomedical imaging devices. 3D patterning methods that precisely assemble nanowires with locally controlled composition and orientation would enable new optoelectronic device designs. As an exemplar, we have created and 3D-printed nanocomposite inks composed of brightly emitting colloidal cesium lead halide perovskite (CsPbX3, X = Cl, Br, and I) nanowires suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 45 publications
(53 reference statements)
0
122
0
Order By: Relevance
“…Colloidal semiconductor nanowires have also been printed with a polystyrene–polyisoprene–polystyrene block copolymer matrix. [ 260 ] The 3D printing process enables good control over the alignment of the nanowire. SAXS result suggests that the printed block copolymer filaments have a long‐range order and an anisotropic structure ( Figure A).…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
“…Colloidal semiconductor nanowires have also been printed with a polystyrene–polyisoprene–polystyrene block copolymer matrix. [ 260 ] The 3D printing process enables good control over the alignment of the nanowire. SAXS result suggests that the printed block copolymer filaments have a long‐range order and an anisotropic structure ( Figure A).…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
“…In contrast, when the polarization is aligned 30° with two nanowire orientations and perpendicular to the third, the pixel array emits two colors (e.g., green‐red). Reproduced with permission 200. Copyright 2019, American Association for the Advancement of Science.…”
Section: Fluid Shear Patterningmentioning
confidence: 99%
“…For example, DIW can be used to orient nanowires to program an optical response to polarized light. Zhou et al programmed the alignment of cesium lead halide (CsPbX3, X = Cl, Br, and I) nanowires with a perovskite crystal structure to form polarized optical architectures 200. The ink consisted of perovskite nanowires suspended in a polystyrene‐polyisoprene‐polystyrene (SIS) block copolymer matrix.…”
Section: Fluid Shear Patterningmentioning
confidence: 99%
“…Halide perovskites with the general formula of APbX 3 (A = MA, FA, and Cs; X = Cl, Br, and I) have been widely adopted in photovoltaics and lighting applications owing to their high absorption coefficient,12 intense photoluminescence (PL) emission,13 controllable optoelectronic property,14 and ability to grow by cost‐effective solution process 15. With elongated 1D structure and high refractive index compared with the environment, perovskite nanowires (NWs) and nanorods are able to emit strongly polarized light 16–19. For instance, Tauber et al reported the polarized emission from an individual MAPbI 3 NW with high degree of linear polarization (DOLP) of 0.7 20.…”
Section: Introductionmentioning
confidence: 99%